Od realnego socjalizmu do kapitalizmu. Mirosława Dzielskiego koncepcja zmiany politycznej - Krystyna Maruszczak (Świat Idei i Polityki, 2007)
The author of the article analyses the idea of political change, focusing on the question whether this change in Poland after the year 1989 was carried out by way of revolution or reforms. he considerations characterise mainly the idea of Mirosław Dzielski and his community, as well as relations with their opponents. Several elements of the above-named theory are brought out in the text. Firstly, the necessity of making comprehensive social changes for the success of the planned change. Secondly, reality diagnosis is necessary. Thirdly, planning of the form of political change, and finally, creation of the project for 'the system of freedom'. The article shows the uniqueness of Dzielski's opinions as a liberal. The author puts special emphasis on the fact that according to him, the reforms program should be directed not at communists but communism. What's more, he perceived that in the Polish conditions there was a collision between freedom and democracy, whereas in his opinion the primacy should go the former.